Significant nocturnal wakefulness after sleep onset in metabolic dysfunction–associated steatotic liver disease - Schaeffer, Sofia; Bogdanovic, Andrijana; Hildebrandt, Talitha; Flint, Emilio; Geng, Anne; Pecenko, Sylvia; Lussier, Paul; Strumberger, Michael A.; Meyer, Martin; Weber, Jakob; Heim, Markus H.; Cajochen, Christian; et al. (Frontiers in Network Physiology, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a multisystemic disease with a multifactorial pathogenesis involving dietary, environmental, and genetic factors. Previous mouse models suggested that circadian misalignment may additionally influence its development as it influences metabolism in diverse organs including the liver. Further, data from sleep questionnaires proved sleep-wake disruption in patients with MASLD. We objectively assessed sleep-wake rhythms in patients with biopsy-proven MASLD (n=35) and healthy controls (HC, n=16) using actigraphy 24/7 for four weeks. With the aim to re-align sleep rhythms a single standardized sleep hygiene education session was performed after two weeks. Actigraphy data revealed that MASLD patients had more awakenings per night (MASLD vs. HC 8.5 vs. 5.5, p=0.0036), longer wakefulness after sleep onset (MASLD vs. HC 45.4 min vs. 21.3 min, p=0.0004), and decreased sleep efficiency (MASLD vs. HC 86.5% vs. 92.8%, p=0.0008) compared with HC despite comparable sleep duration. Patients with MASLD self-reported shorter sleep duration (MASLD vs. HC 6h vs. 6 h 45 min, p=0.01) and prolonged sleep latency contributing to poorer sleep quality. Standardized sleep hygiene education did not produce significant changes in sleep parameters. Our findings indicate fragmented nocturnal sleep in patients with MASLD, characterized by increased wakefulness and reduced sleep efficiency, perceived subjectively as shortened sleep duration and delayed onset. A single sleep hygiene education session did not improve sleep parameters.